Probabilistic approach for assessing infants' health risks due to ingestion of nanoscale silver released from consumer products. (February 2017) - Pang, Chengfang; Hristozov, Danail; Zabeo, Alex; Pizzol, Lisa; Tsang, Michael P.; Sayre, Phil; Marcomini, Antonio
Abstract: Silver nanoparticles (n-Ag) are widely used in consumer products and many medical applications because of their unique antibacterial properties. Their use is raising concern about potential human exposures and health effects. Therefore, it is informative to assess the potential human health risks of n-Ag in order to ensure that nanotechnology-based consumer products are deployed in a safe and sustainable way. Even though toxicity studies clearly show the potential hazard of n-Ag, there have been few attempts to integrate hazard and exposure assessments to evaluate risks. The underlying reason for this is the difficulty in characterizing exposure and the lack of toxicity studies essential for human health risk assessment (HHRA). Such data gaps introduce significant uncertainty into the risk assessment process. This study uses probabilistic methods to assess the relative uncertainty and potential risks of n-Ag exposure to infants. In this paper, we estimate the risks for infants potentially exposed to n-Ag through drinking juice or milk from sippy cups or licking baby blankets containing n-Ag. We explicitly evaluate uncertainty and variability contained in available dose-response and exposure data in order to make the risk characterization process transparent. Our results showed that individual margin of exposures for oral exposure to sippy cups and baby blankets containing n-Ag exhibited minimal risk. Graphical abstract: Highlights: This study demonstrates minimal risk for the infant population exposed to n-Ag. A probabilistic risk assessment approach is used to address uncertainties in HHRA. It is necessary to generate more data to derive nano-specific assessment factors.